Waste Management System: A Case Study of Waste Bank Management Toward a Circular Economy in Maros Regency - Fatmawati, Fatmawati; Ilham, Ilham; Saleh, Syafiuddin; Razak, Andi Rosdianti (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Waste management has been in the spotlight recently due to the annual escalating volume of waste generated. The concept of a circular economy has emerged as a viable economic framework that aligns with sustainable development objectives, particularly those concerning responsible consumption and production practices to support local economies. This article seeks to assess the efficacy of waste bank management in fostering the development of an efficient municipal waste management system conducive to a circular economy with a robust waste recycling infrastructure. This study employed a descriptive qualitative interpretative approach underpinned by a phenomenological framework. Data were gathered from diverse reputable sources such as journals, books, and other relevant references, which the author subsequently analyzed. The findings indicate that waste management in Maros Regency has been operating optimally, driven by stakeholder involvement in promoting waste disposal practices within the community. Establishing the Turikale Main waste bank is a testament to the success of transitioning waste management towards a circular economy model. This initiative facilitates waste recycling and empowers the local economy, generating substantial monthly revenue independently. The significance of this research lies in its capacity to offer valuable insights and recommendations for researchers seeking to evaluate and formulate waste management strategies anchored in the concept of waste banks, which can be replicated in other regions.